2017
DOI: 10.1093/aje/kwx345
|View full text |Cite
|
Sign up to set email alerts
|

Does Strength-Promoting Exercise Confer Unique Health Benefits? A Pooled Analysis of Data on 11 Population Cohorts With All-Cause, Cancer, and Cardiovascular Mortality Endpoints

Abstract: Public health guidance includes recommendations to engage in strength-promoting exercise (SPE), but there is little evidence on its links with mortality. Using data from the Health Survey for England and the Scottish Health Survey from 1994-2008, we examined the associations between SPE (gym-based and own-body-weight strength activities) and all-cause, cancer, and cardiovascular disease mortality. Multivariable-adjusted Cox regression was used to examine the associations between SPE (any, low-/high-volume, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
163
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(170 citation statements)
references
References 47 publications
3
163
1
3
Order By: Relevance
“…The present data add to the evidence base for the health benefits of resistance exercise, which includes a reduction in blood pressure, improvements in blood lipids and an association with lower mortality (Cornelissen, Fagard, Coeckelberghs, & Vanhees, 2011;Stamatakis et al, 2018). Thus, it is clear why the physical activity recommendations include muscle-strengthening activities (World Health Organzation, 2011).…”
Section: Discussionmentioning
confidence: 71%
“…The present data add to the evidence base for the health benefits of resistance exercise, which includes a reduction in blood pressure, improvements in blood lipids and an association with lower mortality (Cornelissen, Fagard, Coeckelberghs, & Vanhees, 2011;Stamatakis et al, 2018). Thus, it is clear why the physical activity recommendations include muscle-strengthening activities (World Health Organzation, 2011).…”
Section: Discussionmentioning
confidence: 71%
“…One of the challenges in establishing the independent and joint effects is that those meeting the muscle strengthening recommendation tend to also be aerobically active. Typically, less than 5% of a nationally representative sample meets the muscle strengthening recommendation only 21,22 . Secondly, there is a need to establish the extent to which activities that improve aerobic fitness are the same as activities that strengthen muscles and improve balance and coordination.…”
Section: Discussionmentioning
confidence: 99%
“…1 The health benefits of cardiorespiratory fitness are well established 2 although less is known about muscle strength. 3,4 Handgrip strength is a valid measure of physical function/ performance that has been widely used in observational cohort studies and clinical settings. [5][6][7][8] Several studies have shown that handgrip strength is inversely associated with risk of mortality [9][10][11] although the mechanisms linking muscle strength and disease outcomes are poorly understood.…”
Section: Introductionmentioning
confidence: 99%